Surgical simulator training reduces operative times in resident surgeons learning phacoemulsification cataract surgery - Cristina Lopez-Beauchamp; Gemini A. Singh; Soo Y. Shin; M. Teresa Magone (American Journal of Ophthalmology Case Reports, 2020)
Purpose: To compare the surgical duration for routine phacoemulsification surgeries in residents with and without virtual simulator training. Methods: Retrospective cohort study of operative times of routine phacoemulsification cataract surgeries performed by 29 different third-year residents rotating at one academic institution. One group underwent mandatory virtual cataract surgery simulator training (SIM) in their second year of residency before starting surgeries while the other group did not undergo any simulator training (NOSIM). Outcomes measured were comparative surgical times and vitreous loss rates between groups in their third year of residency. Results: 722 surgeries were included. Surgeries in the SIM group were on average 6.7 min (min) shorter compared to the NOSIM group (P = 0.0001). Although both groups required less time for surgery over the course of the academic year, regression analysis showed that NOSIM group residents overall required 17% longer time for an uncomplicated clear corneal phacoemulsification surgery (incidence rate ratio 1.17; p = 0.0001). In the final month of their residency residents in the SIM group (32.2 ± 3 min) were 9 min faster than NOSIM peers (41.2 ± 3 min mean ± SE; p = 0.02). Vitreous loss rates were 1.4% in the SIM group and 3.6% in the NOSIM group (p = 0.06). Conclusion and Importance: Early and continuous implementation of mandatory virtual simulator surgical training before starting intraocular surgeries significantly decreases operative times in third year residents learning phacoemulsification compared to non-simulator trained peers.